2002
DOI: 10.1086/340044
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Influenza A (H5N1) Infection among Poultry Workers, Hong Kong, 1997–1998

Abstract: In 1997, outbreaks of highly pathogenic influenza A (H5N1) among poultry coincided with 18 documented human cases of H5N1 illness. Although exposure to live poultry was associated with human illness, no cases were documented among poultry workers (PWs). To evaluate the potential for avian-to-human transmission of H5N1, a cohort study was conducted among 293 Hong Kong government workers (GWs) who participated in a poultry culling operation and among 1525 PWs. Paired serum samples collected from GWs and single s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
214
1
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(228 citation statements)
references
References 16 publications
5
214
1
6
Order By: Relevance
“…Our fi ndings differ from those from a study of poultry workers in Hong Kong, among whom the estimated seroprevalence of infl uenza virus (H5N1) neutralizing antibodies was 10% during the 1997 outbreak (10). The Hong Kong poultry workers, however, likely had much greater intensity of exposure to poultry infected with infl uenza virus (H5N1) than our study population had.…”
Section: Discussioncontrasting
confidence: 99%
“…Our fi ndings differ from those from a study of poultry workers in Hong Kong, among whom the estimated seroprevalence of infl uenza virus (H5N1) neutralizing antibodies was 10% during the 1997 outbreak (10). The Hong Kong poultry workers, however, likely had much greater intensity of exposure to poultry infected with infl uenza virus (H5N1) than our study population had.…”
Section: Discussioncontrasting
confidence: 99%
“…They have included serosurveys of bird cullers, open bird market workers, swine workers, duck hunters, meat processing workers, veterinarians and poultry workers, concluding that these populations are indeed at greater risk of infection with zoonotic influenza virus 5 , 6 , 8 , 9 , 10 , 11 , 12 , 13 …”
Section: Discussionmentioning
confidence: 99%
“…Although the media reported that a corporate-run poultry farm, Biman Poultry Complex, was the fi rst avian infl uenza-affected farm in Bangladesh, our investigation found it to be the third. Of the 5 breeder farms, 2 had imported chicks from the United States and 1 from (6,7), genetic variation in receptors (8)(9)(10), poor surveillance of disease in humans, or using antiviral drugs during culling of birds.…”
Section: The Studymentioning
confidence: 99%